Precision and Accuracy in the Quantitative Analysis of Biological Samples by Accelerator Mass Spectrometry: Application in Microdose Absolute Bioavailability Studies - Gao, Lan; Li, Jing; Kasserra, Claudia; Song, Qi; Arjomand, Ali; Hesk, David; Chowdhury, Swapan K (Analytical chemistry (Washington), 2011)
Determination of the pharmacokinetics and absolute bioavailability of an experimental compound, SCH 900518, following a 89.7 nCi (100 μg) intravenous (iv) dose of 14C-SCH 900518 2 h post 200 mg oral administration of nonradiolabeled SCH 900518 to six healthy male subjects has been described. The plasma concentration of SCH 900518 was measured using a validated LC–MS/MS system, and accelerator mass spectrometry (AMS) was used for quantitative plasma 14C-SCH 900518 concentration determination. Calibration standards and quality controls were included for every batch of sample analysis by AMS to ensure acceptable quality of the assay. Plasma 14C-SCH 900518 concentrations were derived from the regression function established from the calibration standards, rather than directly from isotopic ratios from AMS measurement. The precision and accuracy of quality controls and calibration standards met the requirements of bioanalytical guidance (U.S. Department of Health and Human Services, Food and Drug Administration, Center for Drug Evaluation and Research, Center for Veterinary Medicine. Guidance for Industry: Bioanalytical Method Validation (ucm070107), May 2001. http://www.fda.gov/downloads/Drugs/GuidanceCompilanceRegulatoryInformation/Guidances/ucm070107.pdf). The AMS measurement had a linear response range from 0.0159 to 9.07 dpm/mL for plasma 14C-SCH 900158 concentrations. The CV and accuracy were 3.4–8.5% and 94–108% (82–119% for the lower limit of quantitation (LLOQ)), respectively, with a correlation coefficient of 0.9998. The absolute bioavailability was calculated from the dose-normalized area under the curve of iv and oral doses after the plasma concentrations were plotted vs the sampling time post oral dose. The mean absolute bioavailability of SCH 900518 was 40.8% (range 16.8–60.6%). The typical accuracy and standard deviation in AMS quantitative analysis of drugs from human plasma samples have been reported for the first time, and the impact of these parameters on quantitative analysis was further assessed using the Z factor. The use of the lowest achievable LLOQ Z =0 derived from statistical analysis of the control and low-concentration standards for AMS measurements is proposed in future studies.